Long-term properties of carbon fiber-reinforced shape memory epoxy/polymer composites exposed to vacuum and ultraviolet radiation. (4th October 2019) - Jang, Joon Hyeok; Hong, Seok Bin; Kim, Jin-Gyun; Goo, Nam Seo; Lee, Hanmin; Yu, Woong-Ryeol
Abstract: Shape memory polymer composites (SMPCs) are being evaluated for aerospace applications due to their lightweight and ease of self-deployment. For such applications, the mechanical properties of SMPCs, including long-term behavior, need to be determined in the particularly harsh environments that are likely to be encountered. In this study, the storage modulus of carbon fiber-reinforced SMPCs (CF-SMPCs) was investigated under high vacuum condition and ultraviolet (UV) irradiation. The storage modulus of CF-SMPCs generally degrades as a function of time and temperature. However, the opposite behavior was observed under vacuum and UV exposure due to induced crosslinking. These two phenomena were characterized separately using acceleration tests at various temperatures under UV irradiation in a vacuum chamber and were modeled as two time-temperature superposition laws. The long-term mechanical behavior of CF-SMPCs in vacuum and UV environment is predicted by a linear product of shift factors obtained from the two acceleration tests.